Pendampingan Life Skill Santri Sunan Drajat Lamongan Melalui Pembuatan Bakso Santri - Ulum, Miftachul; Mun’im, Abdul; Kustina, Fariha (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This community assistance activity aims to provide the importance of having personal skills (life skills for one's self, as well as providing skills in making meatballs for Sanan Drajat Lamongan students. This assistance was attended by 20 students who had graduated from SMK or Madrasah Aliayah level. Methods of implementation activities with training on making meatballs and providing material on the importance of having personal skills. Assistance activities are carried out from 2-4 June 2023. As a result of mentoring activities, students have an understanding of the benefits of self-skill education, have skills in making meatballs, are able to work in team work and open up more advanced self-knowledge in creating business opportunities.